Participation in Physical Activity During Center and Home-Based Pulmonary Rehabilitation for People With COPD: A SECONDARY ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL. Issue 2 (March 2019) - Lahham, Aroub; McDonald, Christine F.; Mahal, Ajay; Lee, Annemarie L.; Hill, Catherine J.; Burge, Angela T.; Cox, Narelle S.; Moore, Rosemary; Nicolson, Caroline; O'Halloran, Paul; Gillies, Rebecca; Holland, Anne E.
Abstract : Purpose: To compare levels of physical activity during center and home-based pulmonary rehabilitation (PR) in people with chronic obstructive pulmonary disease. Methods: Forty-five consecutive participants (23 male, n = 20, in the home-based group) with mean age of 68 ± 8 yr and forced expiratory volume in the first second of expiration (FEV1 ) 53 ± 18% predicted undertook physical activity monitoring using the SenseWear Armband during the final week of the interventions of center or home-based PR. Differences in time spent in total physical activity (≥1.5 METs), time spent in moderate to vigorous intensity physical activity (≥3 METs), and steps were compared. Results: Home participants spent a median and interquartile range of 310 (199-328) min/d engaged in total physical activity (29% moderate to vigorous intensity physical activity) compared with 300 (204-370) min/d for the center group (28% moderate to vigorous intensity physical activity, P = .98). Daily step count did not differ between groups (home-based median 5232 [2067-7718] versus center-based median 4049 [1983-6040], P = .66). Of note, center-based participants took 38% more steps on days of program attendance compared with nonattendance days (mean difference: 761 steps/d; 95% CI, −56 to 1579, P = .06). Conclusion: For people with chronic obstructive pulmonary disease undertaking PR, no differences in physical activity levels between center and home-based programs were demonstrated. Understanding the impact of the indirect supervision and motivational interviewing technique utilized during home-based PR on levels of physical activity in people with chronic obstructive pulmonary disease may support clinical implementation of the model as an alternative option to traditional care. Abstract : Although home-based pulmonary rehabilitation (PR) is largely unsupervised, it may produce equivalent outcomes to center-based PR. The impact of indirect supervision on duration and intensity of physical activity during PR is not reported. This study demonstrated no differences in activity levels during the eighth week of center-based and home-based PR.